Behavioral analysis of captive Malayan tapirs (Tapirus indicus) - Kamisan, Norhafizah (2017)
Malayan tapirs (Tapirus indicus) in captivity have been increasing in numbers, especially with their wild populations facing a declining trend. Good management is imperative to ensure their health and welfare is upheld, along with their public image to improve awareness of these animals. Behavioral observations were carried out with the aim of describing the tapirs’ diurnal behavior in captivity. Four Malayan tapirs living as pairs in two exhibits from Zoo Negara, Malaysia, were included in this study. Focal sampling was done with behaviors recorded for six hours during the opening hours of the institution. Additionally, the frequencies of visitors to the exhibits were noted. Diurnal activity budgets, exhibit use, and visitor frequency effects were calculated from the data collected. The data revealed that on average, all four tapirs spent a large amount of time resting, swimming and eating. Neither gender differences nor exhibit differences were observed between the activity levels of the tapirs. A negative correlation between their activity levels and visitor numbers were also identified. These findings may be explained by the tapirs having been bred in captivity, and having adapted to the presence of humans. The results conformed to the tapirs’ expected crepuscular behavior, with no stereotypic behaviors seen.